HUBUNGAN ANTARA BERPIKIR POSITIF DENGAN ACTIVE COPING BEHAVIOR - May Agus Swandono (Ilmu Psikologi Universitas Yudharta Pasuruan)
Active coping with free behavior to solve problems, pressures, or challenges, besides it is a protective response, which enhances dynamic behavior. Think positively about one's efforts in giving thought on a problem, that was raised about something normal and tried to be heartened with the necessary skills, to increase awareness, about seeing the beneficial aspects of every problem that occurs. The purpose of this study was to determine the relations between positive thinking with active treatment teenager in a junior high school in Pasuruan district. The population in this study used 35 children using one class and all participants were sampled. The method of getting information used is positive scale conversation and active coping. The validity test in this study used the product moment experimental formula. The scale of active coping behavior has a validity coefficient between 0.337 to 0.636, while the positive thinking scale is between 0.342 to 0.652. For the reliability test using Hoyt, rxx '= 0.715 (active coping behavior), rxx' = 0.819 (positive learning) with r table 1% = 0.430 and 5% = 0.334 (N = 35).Where as the data analysis uses 1 predictor regression analysis. The results of this study can be obtained F-count value of 0.474 with F-table 1% = 4.08 and 5% = 2.45. denied that there is no relationship between positive thinking with active coping behavior (not significant), then in this case a hypothesis which states that "there is a relationship of positive thinking with active coping behavior", is not accepted. So active coping behavior, which is conducted by someone will depend on several other factors.